PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH CU CINTA KASIH TIGAPANAH - Mariska, Refi; Sitanggang, Darna (Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine and explain the effect of the service marketing mix on customer decisions to choose CU Cinta Kasih Tigapanah. The analysis method used is multiple linear regression. The population in this study were customers of CU Cinta Kasih Tigapanah during 2015-2018, totaling 10,500 people. The sampling method uses the desired maximum error. So the number of customers who were sampled was 96 people. Data collection techniques using questionnaires, interviews and documentation study. From the research results, the multiple linear regression equation is obtained as follows: Y = 1,848 + 0.304X1 + 0.091X2 + 0.018X3 + 0.034X4 + 0.354X5 + 0.440X6 + 0.237X7 + e.This means that the process variable (X5) has the greatest influence on customer decisions, where the largest regression coefficient is 0.354. Based on the t test, the product has a positive but not significant effect on customer decisions where the significance value is 0.061> 0.05. Price, location, promotionand physical evidence has a positive but not significant effect on customer decisions. People and process has a positive and significant effect on customer decisions. The results of the F test show that the product, price, location, promotion, people, process, physical evidence have a positive and significant effect on the customer's decision to choose CU Cinta Kasih Tigapanah. The value (R square) is 0.85, meaning that the variations in the customer's decision to choose CU Cinta Kasih Tigapanah can be explained by the product, price, location, promotion, people, process, and physical evidence of 85.4%, and the remaining 14.6% can explained by other variables not included in this study such as service quality and marketing strategy.